February–May 2019. (September 2019) - Cranmer, Frank
Abstract : The Civil Partnerships, Marriages and Deaths (Registration Etc.) Bill, originally introduced by Tim Loughton MP as a private Member's bill in the Commons, received Royal Assent on 26 March and came into force two months after it was passed. Section 1 empowers the Secretary of State to amend by regulations the Marriage Act 1949 to provide for a central register of marriages in England and Wales 'which is accessible in electronic form'. Section 2 requires the Secretary of State to amend the Civil Partnership Act 2004 so that opposite-sex couples become eligible to form a civil partnership in England and Wales – and the amending regulations must be in force no later than 31 December 2019. Section 3 requires the Secretary of State to report on whether the law should be changed to allow the registration of pregnancy losses which cannot be registered as stillbirths under the Births and Deaths Registration Act 1953 and section 4 requires the Secretary of State to make arrangements for the preparation of a report on whether, and if so how, the law should be changed to enable or require coroners to investigate stillbirths.